Are we respecting the wishes of older persons who are living in residential aged care? - Masters, Stacey; Brown, Margaret; Grantham, Hugh; Roberts, Louise; Pirone, Christy (Royal Commission into Aged Care Quality and Safety, 2019)
Older persons living in residential aged care are frequent users of ambulance services and hospital emergency departments (ED). A clinical audit of 300 randomly selected presentations from aged care to ED found that residents were often transferred to hospital against their values, preferences and directions expressed in their advance care plan or advance care directive. This submission to the Royal Commission into Aged Care Quality and Safety highlights problems with the number of different advance care planning forms in use as well as problems with interpretation of the documents.